Energy Analysis of Physical Absorption and Chemical Absorption of CO2 in Ionic Liquids. Issue 1 (1st October 2019) - Xie, Yujiao; Liu, Gang; Nie, Haiwei; Yu, Fangyong; Xing, Xiaoxue; Cui, Hongyou
Abstract : CO2 solubility in ionic liquids (ILs) is measured extensively to develop IL‐based technology for CO2 capture. Herein, the choline‐ and acetate‐based ILs are selected as the studied physical and chemical absorbents for CO2 capture, respectively. The CO2 solubilities in choline‐ and acetate‐based ILs are thermodynamically modeled. The ILs consumed for CO2 absorption and the energy demands for the ILs regeneration are calculated and compared with those of the conventional imidazolium‐based ILs. The results show that the three choline‐based ILs are not energy saving in the pressure‐swing process. In the temperature‐swing process, the energy demand for CO2 absorption by using acetate‐based ILs reveals that the chemical absorption‐based ILs are the absorbent with lower energy demands compared with the physical absorption‐based ILs. Abstract : The physical absorption of CO2 in choline‐based ionic liquids (ILs) and the chemical absorption of CO2 in acetate‐based ILs is studied. The energy demands of CO2 in both pressure‐ and temperature‐swing processes are calculated. The results show that the acetate‐based ILs are effective both in terms of the amount of ILs consumed and the total energy demands.